2020
DOI: 10.2355/isijinternational.isijint-2020-173
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution and Mechanical Properties Improvement in Magnetic-controlled Electroslag Remelted Bearing Steel

Abstract: The transverse static magnetic field (TSMF) was introduced into the electroslag remelting (ESR) process to produce GCr15 steel ingots and the microstructure, non-metallic inclusions, chemical composition and mechanical properties of the ingots were analyzed to investigate the effect of TSMF during the ESR process. The transverse section of the ingots indicated that the application of a 130 mT static magnetic field resulted in a refined dendritic structure. The coverage ratio of the homogeneous crystallites are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Khiavi et al 10) showed that the total content of oxygen, nitrogen and hydrogen continuously decreased with the increasing refining time or the addition of calcium during vacuum induction refining. Guo et al 11) and Li et al 12) obtained high-purity ingots by applying a transverse static magnetic field (TSMF) during the electroslag remelting (ESR). The thickness of the liquid melting film (LMF) was decreased in the presence of the TSMF, meanwhile the kinetic conditions for inclusion removal were also enhanced.…”
Section: Influence Of Microsegregation On the Tin Inclusions Formatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Khiavi et al 10) showed that the total content of oxygen, nitrogen and hydrogen continuously decreased with the increasing refining time or the addition of calcium during vacuum induction refining. Guo et al 11) and Li et al 12) obtained high-purity ingots by applying a transverse static magnetic field (TSMF) during the electroslag remelting (ESR). The thickness of the liquid melting film (LMF) was decreased in the presence of the TSMF, meanwhile the kinetic conditions for inclusion removal were also enhanced.…”
Section: Influence Of Microsegregation On the Tin Inclusions Formatio...mentioning
confidence: 99%
“…( 12). 39) λ 2 = A f n t ................................. (12) where A = 6.79 × 10 − 6 m/s n and n = 0.43.…”
Section: Growth Model Of Tin Inclusionsmentioning
confidence: 99%
“…Compared to the imposed alternating MF (electromagnetic stirring) or pulsed MF on the ESR process proposed by other researchers [36,37], because skin effect (due to the water-cooled mold) tends to happen with the application of alternating or cyclic MF, there is a significant benefit for static MF. Such technology is currently being investigated for a variety of steel grades including low-alloyed GCr15 bearing steel [38,39], medium-alloyed H13 die steel [40,41], and high-alloyed M2 HSS [42,43]. Guo et al [42,43] applied a transverse static MF (TSMF, with different magnetic flux densities) for regulating M2 HSS solidification upon ESR.…”
Section: Introductionmentioning
confidence: 99%